Persepsi Mahasiswa Terhadap Penggunaan Kamus Digital Bahasa Arab Di Era Society 5.0 - Ahmad Arifin; Slamet Mulyani (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2021)
The Arabic dictionary is the primary reference for students learning Arabic, mainly when translating. With advances in technology, dictionaries are no longer in sheets of paper but in digital form that mobile phones and desktops can be accessed. This study aimed to determine students' perceptions of the use of digital dictionaries and various aspects of the difficulties experienced by students. This exploratory research was conducted using a survey technique on randomly selected students, and a descriptive technique was used as an analytical tool. The number of respondents is as many as 100 students from 2 different universities. In general, answers related to students' perceptions can be mapped in several ways: 1) students’ ability to translate is still low. 2) students still have many difficulties when translating and how to use a dictionary. 3) dictionaries are still required, both digital and print. 4) google translate became the student's favorite dictionary. So, the author recommends special training in dictionaries at the beginning of lectures at the higher education level.